Self-assembly of biohybrid polymers - Kedracki, Dawid; Abraham, Jancy Nixon; Prado, Enora; Nardin, Corinne (Macromolecular self-assembly, 2016)
Self-assembly is considered to be the process through which building blocks spontaneously organize into well-defined frequently functional structures. The tailoring of properties of such structures has drawn attention in various fields, in particular, in enzymatic cascade reactions, drug delivery, amphiphilic copolymer nanocontainers, and nanoreactors. Polymer-DNA hybrid self-assemblies, in addition to responsiveness to ionic strength, are sensitive to hybridization, which renders the establishment of a theoretical framework challenging when both specific hydrogen bonding between complementary sequences and association are to be taken into consideration. Numerous various highly characterized self-assemblies are recognized to organize through nucleation dependent polymerization, including microtubule formation, sickle-cell fibril formation, flagellum assembly, among others. Interpolyelectrolyte complexes (IPECs) have attracted attention due to the large number of emerging and potential applications. Environmental factors such as the medium also play a role in the complex formation process, especially pH and ionic strength.

Self-assembly of novel Fmoc-cardanol compounds into hydrogels - analysis based on rheological, structural and thermal properties - Kadeeja, Aliya; Joseph, Seena; Abraham, Jancy Nixon (Soft Matter, 2020)
Hydrogels of low molecular weight molecules are particularly appealing for various biomedical applications such as drug delivery, tissue engineering, and antitumor therapy due to their excellent biocompatibility, biodegradability, and easy availability. Fmoc-peptide hydrogels form an essential category of these hydrogels. Herein we report a new class of Fmoc hydrogels in which cardanol (3-pentadecyl phenol (PDP)) is covalently linked with fluorenylmethyloxycarbonyl group. Cardanol is a plant-based renewable raw material, readily obtained from Cashew Nut Shell Liquid (CNSL). The long aliphatic chain of pentadecyl phenol helps in bringing a structural incompatibility and generates different nanostructures such as nanospheres, nanotapes, and nanofibers depending on Fmoc substitution and the solvents used. Stable hydrogels were formed from Fmoc-PDP in DMSO/H2O, and the critical aggregation concentration (CAC) and critical gelation concentration (CGC) were determined. The role of non-covalent forces such as hydrogen-bonding, hydrophobicity, and pi-pi stacking interactions in governing self-assembly to hydrogel formation was studied for Fmoc, DiFmoc and Boc groups attached to PDP. The thermal properties were analyzed, and smectic and nematic phases were identified for the molecules depending on the substitutions involved. Overall the study supports the mechanisms of aggregation and gelation in novel Fmoc-cardanol derivatives.